Natural resource management (NAREM)- an insight - Omar, Ismail (Fakulti Kejuruteraan Dan Sains Geoinformasi, 2007)
Natural resource management, conservation and restoration are applications of ecological principles by humans. Judgment of success is from the human perspective. The scale of application is variable within the "human scale" of activity - yet manifested and viewed from global down to small acreages and households, even to the microscopic. Regulations and laws may be assets, or impediments, depending on their adaptability to local and temporal conditions and subject to skillful implementation over time. Economics may produce strong forces that support or undermine success. The perspective of individuals or groups of individuals often conflict with the needed changes and management activities. Although conservation and restoration are science based activities, we know far less than we need to have a routine procedure to follow. Therefore, our management actions must address the processes of conservation and restoration on an appropriate scale and then be maintained for an extended time with appropriate mid-course corrections for our ecological objectives to be approached.